Night Eating Syndrome in Patients With Obesity and Binge Eating Disorder: A Systematic Review - Kaur, Jasmine; Dang, An Binh; Gan, Jasmine; An, Zhen; Krug, Isabel (Frontiers in Psychology, 2022)
Night eating syndrome (NES) is currently classified as an Other Specified Feeding or Eating Disorder (OSFED) under the Diagnostic Statistical Manual−5 (DSM-5). This systematic review aims to consolidate the studies that describe the sociodemographic, clinical and psychological features of NES in a population of patients with eating disorders (ED), obesity, or those undergoing bariatric surgery, and were published after the publication of the DSM-5. A further aim was to compare, where possible, NES with BED on the aforementioned variables. Lastly, we aimed to appraise the quality of the studies being included in the review. We conducted a systematic search on three databases (MEDLINE, PubMed and Embase) which resulted in the selection of 22 studies for the review. We included the articles that studied patients with NES and their sociodemographic, clinical and psychological features in a clinical (i.e., ED, obese or bariatric surgery) population, through a quantitative study design. Articles were excluded if the NES patients included in the study had a comorbid psychological disorder, and/or the sample was collected from a university/non-clinical population, and/or the study design was qualitative, and/or NES features were compared with any other disorder, except BED. Our study found that no conclusions about the link between any sociodemographic feature (such as, age, gender, income, etc.) and an NES diagnosis could be made. Further, NES patients presented with elevated ED pathology (including emotional eating and loss of control eating) and higher occurrence of depressive symptoms than controls. Contrary to the literature suggesting that NES and Binge Eating Disorder (BED; an ED subtype which is also comorbid with obesity) patients often report overlapping features, questioning the validity of NES as an ED diagnosis, we found that BED can be differentiated from NES by the higher occurrence of emotional eating, body related concerns and abnormal eating episodes. The review also suggested an overlap between NES and Sleep-Related Eating Disorder. We recommend that it is essential to study NES as an independent disorder to further develop its diagnostic criteria and treatment options, thereby, increasing the quality of life of the patients suffering from this syndrome.